2017
DOI: 10.1002/anie.201709020
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Wafers with Facet‐Dependent Electrical Conductivity Properties

Abstract: By breaking intrinsic Si (100) and (111) wafers to expose sharp {111} and {112} facets, electrical conductivity measurements on single and different silicon crystal faces were performed through contacts with two tungsten probes. While Si {100} and {110} faces are barely conductive at low applied voltages, as expected, the Si {112} surface is highly conductive and Si {111} surface also shows good conductivity. Asymmetrical I-V curves have been recorded for the {111}/{112}, {111}/{110}, and {112}/{110} facet com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…[7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive. [19] The results are consistent with previous DFT calculations showing metal-like band structuresf or these two Si surfaces. [20] Because germanium is also an important wafer material, knowing the presence of facet-dependent electrical properties of germanium should be quite useful for novel integrated circuit fabrication.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…[7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive. [19] The results are consistent with previous DFT calculations showing metal-like band structuresf or these two Si surfaces. [20] Because germanium is also an important wafer material, knowing the presence of facet-dependent electrical properties of germanium should be quite useful for novel integrated circuit fabrication.…”
Section: Introductionsupporting
confidence: 92%
“…Figure offers band structures of one to three layers of Ge(211) planes, the corresponding DOS plots, and side‐ and top‐view models of the Ge(211) planes. Since germanium and silicon have the same crystal structure, the previous assignment of the Si(112) plane could have been changed to Si(211) planes according to the presence of the (422) peak in the X‐ray diffraction pattern of silicon . The Supporting Information provides band structures of four to six layers of Ge(211) planes, the corresponding DOS plots, and models of the Ge(211) planes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a Cu 2 O octahedron is highly conductive, but a single Cu 2 O rhombic dodecahedron is insulating. More recently, intrinsic Si and Ge wafers have also revealed facet‐dependent electronic properties . All these semiconductors, including Ag 3 PO 4 crystals, display current‐rectifying effects when electrical contacts are made on two different crystal faces .…”
Section: Introductionmentioning
confidence: 99%